Genotypic Features of Clinical and Bovine Escherichia coli O157 Strains Isolated in Countries with Different Associated-Disease Incidences - Pianciola, Luis (2018)
Fil: Pianciola, Luis. Subsecretaría de Salud de Neuquén. Laboratorio Central; Argentina.